Eudragit E100® potentiates the bactericidal action of ofloxacin against fluoroquinolone-resistant Pseudomonas aeruginosa - Romero, Verónica Leonor (2012)
We report the enhanced bactericidal activity of ofloxacin in drug-containing Eudragit E100® dispersions (EuCl-OFX) against Pseudomonas aeruginosa and the effect of the cationic polymer on bacterial membrane. Organisms treated with EuCl-OFX showed changes in cell morphology, altered outer membrane (OM) and cytoplasm with low electrodensity areas. Zeta potential of bacterial surface was shifted to positive. Sensitization to lytic agents was also observed. A profound effect on bacterial size, granularity and membrane depolarization was found by flow cytometry. Cultures exposed to drug-free polymer also showed some damaged bacterial membranes, but there was no significant cell death. Inhibition of P. aeruginosa by EuCl-OFX may involve surface effect and, to some extent, permeation effect. The cationic polymer act to mitigate the electronegativity of cell surface in the process of disorganizing the OM, rendering it more permeable to antibiotic. In addition, cytoplasmic membrane depolarization turns bacterial cell more vulnerable. The effects on membranes combined with the mechanism of action of quinolone explain the improved bactericidal action exhibited by EuCl-OFX. The behavior described for Eudragit E100® against P. aeruginosa may be a useful tool to broaden the spectrum of antibiotics whose clinical use is limited by the impermeability of the bacterial OM.